(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article focuses on the international practices of managing and regulating the housing and community services market. This study examines the international practices of changing housing and community services, as well as the concepts of housing administration in nations including Germany, Hungary, Czech Republic, Poland, Great Britain, and France. The author examines the different approaches to regulating and managing housing and communal economy in foreign countries. They identify the specific characteristics of reforming the housing and communal economy in Central and Eastern European countries that share similar economic development conditions with Russia. The author also investigates the experiences of the housing and communal economy reform in Central and Eastern European countries. The study focuses on the economic development and examines the reforms implemented in Western European nations. It aims to identify the potential for utilizing foreign expertise in reforming the housing and community economy. The potential for using foreign expertise in the reformation of the domestic housing and communal sector. The article provides concrete suggestions for enhancing the involvement of self-organization bodies of the population in managing this sector, as well as ensuring an improvement in the quality of housing and communal services, based on the study conducted. The provision of housing and communal services to the population is of high quality.